Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
See the explanation below.
Explanation:
By means of Hooke's second law, we can calculate the spring constant with the initial conditions of the problem.
[tex]F=k*x[/tex]
where:
k = spring constant [N/m]
x = distance = 0.01 [m]
F = force or weight [N]
Weight can be calculated by means of the product of mass by gravitational acceleration.
m = mass = 500[g] = 0.5[kg]
[tex]W=F=m*g\\W = 0.5*9.81\\W= 4.905[N][/tex]
Now the spring constant can be calculated:
[tex]k=F/x\\k=4.905/0.01\\k = 490.5[N/m][/tex]
We must now use the same Hooke's law to determine the new spring force when stretching it 0.03 [m]
[tex]F_{new}=k*x\\F_{new}=490.5*0.03\\F_{new}=14.715[N][/tex]
Now we have to use Newton's second law to calculate acceleration. We must remember that Newton's Second Law tells us that the sum of forces is equal to the product of mass by acceleration.
[tex]F=m*a[/tex]
where:
F = Fnew = 14.715[N]
m = mass = 500 [g] = 0.5 [kg]
a = acceleration [m/s²]
Now replacing:
[tex]14.715=0.5*a\\a=14.715/0.5\\a=29.43[m/s^{2} ][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.